Materiality conflicts in dual suistanability-reporting regimes: indonesia’s transition from impact-based OJK rules to ISSB financial materiality - Chandra Erick Manaek Pandapotan Lumban Gaol; Tarsisius Murwadji; Beniadi Setiawan (Indonesian Institute For Counseling, Education and Therapy, 2026)
The contemporary architecture of corporate sustainability reporting is undergoing an unprecedented epistemological rupture, transitioning from a localized, impact-oriented paradigm under the Indonesian Financial Services Authority (OJK) toward a globally standardized, financial-materiality framework promulgated by the International Sustainability Standards Board (ISSB). This paradigm shift, culminating in the ratification of PSPK 1 and PSPK 2 effective January 1, 2027, precipitates a profound jurisprudential paradox regarding regulatory compliance and corporate fiduciary duties within emerging markets. Traditional orthodox normative legal research has systematically failed to decode the sociological frictions inherent in this dual-regime landscape, often falsely dichotomizing the frameworks as either mutually exclusive or seamlessly harmonized (Abhayawansa, 2022; Adams & Mueller, 2022). Eradicating these archaic theoretical lacunae, this research operationalizes a cutting-edge methodological fusion, integrating Socio-Legal Analysis with Project-Based Legal Epistemology. By dissecting the